2015
DOI: 10.1093/jscr/rjv028
|View full text |Cite
|
Sign up to set email alerts
|

Metastases of lobular breast carcinoma in the terminal ileum and ileocaecal valve

Abstract: Gastrointestinal (GI) metastases from primary breast carcinoma are rare but more common in invasive lobular carcinoma than invasive ductal carcinoma. The symptoms may be non-specific and the presentation can occur many years after the initial primary breast carcinoma. Radiological and endoscopic findings can be difficult to distinguish from inflammatory bowel disease and primary carcinoma of the GI tract. Histological and immunohistopathology assessment will usually confirm the diagnosis of metastatic breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Breast cancer is the second most common cancer to metastasise to the GI tract, second only to malignant melanoma [2,3] . ILC accounts for 10–20% of breast tumours and is the most likely breast cancer to metastasise due to its loss of cell–cell adhesion molecules [4] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Breast cancer is the second most common cancer to metastasise to the GI tract, second only to malignant melanoma [2,3] . ILC accounts for 10–20% of breast tumours and is the most likely breast cancer to metastasise due to its loss of cell–cell adhesion molecules [4] .…”
Section: Discussionmentioning
confidence: 99%
“…The risk of local or distant metastasis is 60% at the time of first presentation and 30–80% will develop distant metastases after completing the treatment for cancer [5,6] . Although the usual sites for any breast cancer metastases are liver, bone, lungs, brain and nodes [1,2] , secondary deposits to the GI tract have been previously documented, but are certainly a rare entity. Borst and Ingold, in their study of 2604 cases of breast cancer had reported GI metastases in only 17 cases (0.7%) [7,8] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…La biopsia debe ser profunda, ya que las metástasis, a diferencia de los tumores primarios, comienzan por afectar la serosa y la submucosa. Una mucosa intacta con serosa invadida por células tumorales histológicamente idénticas a las del tumor primario de mama confirma el diagnóstico de metástasis 9 . De igual forma, si hay receptores hormonales tanto en el cáncer de mama primario como en la tumoración de colon, se confirma el origen metastásico de esta última.…”
Section: Discussionunclassified